Construction of a novel exosomes-related gene signature in hepatocellular carcinoma - Tao, Qiqi; Zhu, Kai; Zhan, Yating; Zhang, Rongrong; Lang, Zhichao; Yu, Zhengping; Wang, Meng (Frontiers in Cell and Developmental Biology, 2022)
Abstract Background: Exosomes are extracellular vesicles between 40-150 nm in diameter and are cargoes for a wide range of small biological molecules. Recent studies have reported that lncRNAs, miRNAs, circRNAs in serum exosomes may serve as biomarkers to predict hepatocellular carcinoma (HCC) prognosis. However, the prognostic values of exosomal mRNAs in HCC are still unclear. Methods: Data of HCC patients were downloaded from TCGA database. The serum exosome sequencing data of HCC patients and healthy individuals were obtained from the exobase database. Univariate cox regression analysis was used to identify prognosis-related exosomal genes. LASSO and multivariate cox regression analyses were applied to construct prognostic signature. Results: 22 exosomal mRNAs differentially expressed between HCC tissues and normal tissues were identified. Then 8 prognosis-related exosomal mRNAs were screened. Subsequently, G6PD and ADAMTS5, selected by LASSO and multivariate cox regression analyses, were used to construct a prognostic signature. The patients with high-risk scores had a poor prognosis in TCGA cohort as well as ICGC cohort. Notably, this prognostic signature was also validated in a local cohort collected from the First Affiliated Hospital of Wenzhou Medical University. Receiver Operating Characteristic (ROC) analyses indicated that the signature had a good performance in all the cohorts. The gene set enrichment analysis (GSEA) revealed that this signature was associated with cell cycle and metabolism pathways. Immune infiltration analysis indicated that the patients with high-risk scores had a higher M0 macrophages infiltration. The univariate and multivariate cox regression analyses identified the risk score is an independent risk factor. In addition, a nomogram containing age, gender, stage and risk score was constructed to precisely predict HCC prognosis. Conclusion: In conclusion, we develop a novel exosomes-related gene signature that helps to predict the prognosis. Keywords: Hepatocellular carcinoma, Exosome, Prognostic Signature, Immune infiltration，Nomogram.